An Investigation of the Fresh and Hardened Properties of Nano Zinc Oxide Reinforced 3D Printed Geopolymer Mortars - Seloğlu, Maksut (My University, 2024)
It is well known that even small amounts of nanomaterials can improve the mortar structure and enhance its fresh state and hardened properties. This paper investigates the fresh state and hardened properties of nano zinc oxide-reinforced 3D-printed geopolymer mortars. The mechanical properties of 7, 28, 90, and 180 days of 3D-printed geopolymer mortars cured at ambient temperature were investigated. For this purpose, 3D-printed geopolymer mortar samples containing 0%, 0.25%, 0.50%, and 0.75% nano zinc oxide were produced. Flow table and buildability tests were applied to these samples to determine the fresh state properties. Ultrasonic pulse velocity, flexural strength, and compressive strength tests were applied to the hardened 3D-printed geopolymer mortar samples. The best mechanical test results were obtained from 3D-printed geopolymer mortar samples containing 0.5% nano zinc oxide at the end of all curing times. In the ZN 50 series cured for 28 days, approximately 29% higher strength was obtained in FS and 66% higher in compressive strength compared to the ZN 0 series without nanomaterials. It has been noted that incorporating a tiny quantity of nano zinc oxide into 3D-printed geopolymer mortars improves their mechanical performance.
Keywords: Compressive strength; Flexural strength; Buildability; 3D-printed geopolimer mortar; Nano zinc oxide